A Geospatial analysis of solar energy potentials: a case study of Kaduna State, Nigeria - Dabo, Shu’aibu; Narimah Samat,; Kibon, Usman Adamu (Penerbit Universiti Kebangsaan Malaysia, 2024)
Access to clean, sustainable and environmentally friendly energy is a precondition for attaining sustainable development and ensuring climate change mitigation. Renewable energy potentials in Nigeria provides sustained alternative energy sources. In this study, current perspectives of solar energy potentials as a renewable energy option in Nigeria were examined and discussed within the context of Kaduna state. Geospatial techniques were applied to map the solar energy potential sites of the study area using the spatial analysis tools in ArcGIS Pro software 3.0. Results from the study revealed a strong correlation between the ground and satellite measured solar monthly mean daily values of global solar radiation, indicating that Kaduna state has significant potential for harnessing solar energy. The analysis revealed that the maximum insolation values in Kaduna State were recorded between the Months of February, March and January, indicating that the optimum times for harnessing solar energy in the area are the months of February and March. The Pearson correlation coefficient |R| between the observed ground data and the satellite analysis is 0.937, which indicate strong positive correlation the ground and satellite measured solar radiation data, indicating a high evidence of solar energy potentials. This implies that in the absence of one source of radiation data, the other source can reliably serve as alternative. Further analysis revealed that the solar energy potential sites in the state can be classified into areas of high, moderate and low potentials.